Innate Immunity to Respiratory Infection in Early Life - Lambert, Laura; Culley, Fiona J. (Frontiers in Immunology, 2017)
Early life is a period of particular susceptibility to respiratory infections and symptoms are frequently more severe in infants than in adults. The neonatal immune system is generally held to be deficient in most compartments; responses to innate stimuli are weak, antigen presenting cells have poor immunostimulatory activity and adaptive lymphocyte responses are limited, leading to poor immune memory and ineffective vaccine responses. For mucosal surfaces such as the lung, which is continuously exposed to airborne antigen and to potential pathogenic invasion, the ability to discriminate between harmless and potentially dangerous antigens is essential, to prevent inflammation that could lead to loss of gaseous exchange and damage to the developing lung tissue. We have only recently begun to define the differences in respiratory immunity in early life and its environmental and developmental influences. The innate immune system may be of relatively greater importance than the adaptive immune system in the neonatal and infant period than later in life, as it does not require specific antigenic experience. A better understanding of what constitutes protective innate immunity in the respiratory tract in this age group and the factors that influence its development should allow us to predict why certain infants are vulnerable to severe respiratory infections, design treatments to accelerate the development of protective immunity and design age specific adjuvants to better boost immunity to infection in the lung.